2015
DOI: 10.3390/molecules20046454
|View full text |Cite
|
Sign up to set email alerts
|

An Ultra-High Performance Liquid Chromatographic-Tandem Mass Spectrometric Method for the Determination of Sinomenine in Human Plasma after Transdermal Delivery of the Zhengqing Fengtongning Injection

Abstract: A sensitive, precise and selective ultra-high performance liquid chromatography method coupled with triple-quadrupole mass spectrometry was developed and validated for the determination of trace amounts of sinomenine (ng/mL) in minute volumes of human plasma. Fifty microliter plasma samples were precipitated using methanol to extract sinomenine. Separation was carried out on a C18 column with a water and acetonitrile mobile phase gradient with formic acid as an additive. The mass spectrometry data were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Quantification was performed via the multiple reaction monitoring of the transitions of m/z 330.2→239.1 and m/z 330.2→181.0 for SH34 and m/z 289.0→97.1 for IS. Collision energy was set at 26 for SH and 18 for IS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification was performed via the multiple reaction monitoring of the transitions of m/z 330.2→239.1 and m/z 330.2→181.0 for SH34 and m/z 289.0→97.1 for IS. Collision energy was set at 26 for SH and 18 for IS.…”
Section: Methodsmentioning
confidence: 99%
“…The main MS/MS working parameters in the positive mode (1–4.7 min) were set as follows: 3.5 kV capillary voltage, 500 V nozzle voltage, 300°C gas temperature, 300°C sheath temperature, 12 L/min sheath gas flow, and 10 L/min gas flow. Quantification was performed via the multiple reaction monitoring of the transitions of m/z 330.2→239.1 and m/z 330.2→181.0 for SH 34 and m/z 289.0→97.1 for IS. Collision energy was set at 26 for SH and 18 for IS.…”
Section: Methodsmentioning
confidence: 99%
“…Sinomenine is an alkaloid derived from the Chinese herb sinomenium acutum, whose anti-inflammation effects have been widely evaluated and confirmed. Sinomenine has been used in a series of proprietary Chinese medicines for treating rheumatoid arthritis and other autoimmune diseases due to its anti-inflammatory and immunosuppressive properties [12] . Herein, we have designed a RCT protocol to compare the clinical efficacy of sinomenine and colchicine for prophylaxis of acute flares when initiating urate-lowering therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These preparations include sustained-release tablets, injections, and new preparations that can be used for intraarticular administration. [32][33][34][35][36] In clinical settings, SIN preparations are used for RA treatment with evident curative effects and no severe side effects. 37 In our previous study, we observed that the anti-inflammatory effects of SIN can be arrested by -BTX and 7…”
Section: Discussionmentioning
confidence: 99%
“…SIN, an alkaloid derived from a traditional Chinese herb that has been used for centuries in China, is consumed via different kinds of clinical preparations, such as Zhengqing Fengtongning tablets and injections. These preparations include sustained‐release tablets, injections, and new preparations that can be used for intra‐articular administration 32‐36 . In clinical settings, SIN preparations are used for RA treatment with evident curative effects and no severe side effects 37 .…”
Section: Discussionmentioning
confidence: 99%